The twilight saga. Breaking dawn. Part 1 [videorecording (DVD)] - Condon, Bill, 1955-; Stewart, Kristen, 1990-; Pattinson, Robert, 1986-; Lautner, Taylor, 1992-; Burke, Billy; Facinelli, Peter, 1973-; Meyer, Stephenie, 1973- (Summit Entertainment, 2012)
In the highly anticipated fourth installment of the Twilight Saga, a marriage, a honeymoon, and the birth of a child bring unforeseen and shocking developments for Bella and Edward and those they love, including new complications with young werewolf Jacob Black.